THE ROLE OF THE DOCTOR STILL NEEDS IN THE DEVELOPMENT OF THE ARTIFICIAL INTELLIGENCE ERA - Fitriana Jaelani; Sitri Djuma R. Tomu (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
The role of doctors is often questioned as a result of the development of the Artificial Intelligence Era as if the Artificial Intelligence Era will be able to replace the role of doctors. Based on this phenomenon, the research team wishes to conduct research on whether the role of doctors is still necessary in the development of the Artificial Intelligence Era. This research was conducted using qualitative research methods, namely by interviewing informants from several doctors, clinical and pre-clinical students. Data collection techniques by means of in-depth interviews. Sampling by means ofpurposive sample. This study aims to reveal that the role of doctors is still very important in the midst of the development of the Artificial Intelligence Era. The results show that the role of doctors in the development of the Artificial Intelligence Era has a positive role in that Artificial Intelligence is more sophisticated and makes it easier for doctors to carry out their duties. The Artificial Intelligence Era cannot replace the role of doctors, but the Artificial Intelligence Era supports the role of doctors in carrying out their duties.